OpenVMS with Apache, OSU and WASD - Winston, Alan. (Burlington, MA : Digital Press, 2003)
Whether you're an experienced webmaster new to OpenVMS or an old OpenVMS hand new to webservers, this book will save you time and help you do your job better. The book points out similarities and differences between Unix and VMS, contains a management-friendly explanation of VMS's suitability for 24x7 operation, explains web concepts like authentication and access control models clearly (including honest discussion of drawbacks and weaknesses). Clear examples show how to configure each of the three webservers to accomplish specific goals, and comparisons will help you choose which server to run. If you're using or considering using a VMS webserver, this book is for you. OpenVMS with Apache, OSU and WASD also discusses specific tasks, such as how to port CGI programs from other operating systems, and gives working examples in PERL, Python, and DCL. One chapter also covers database connectivity for VMS-based CGI programs. Use OpenVMS to provide reliable, full-featured web service for your business Find information not available anywhere else for OpenVMS, whose unbeatable reliability makes it the web server of choice for institutions that can't afford downtime for their websites Learn from numerous examples and step-by-step procedures how to do the same task in different servers.
Introduction; Why Run a Web Server on VMS?; VMS and the Web; Web Options; Installation Issues; Basic Configuration and Server Control; Encrypted/Secure Communications: HTTPS Protocol Support; Managing Access to your Server Resources; Providing User Personal Web Directories; Multihosting and Multihoming; Indexing and Searching Your Site; Cache and Proxy; Managing and Understanding Your Server Logs; Dynamic Content: Directory Browsing and Server-Side Includes; Running CGI Programs; RDB Database Access from CGI Scripts; Useful Freeware CGI Scripts; High-Performance Scripting Options; User-Edited Web Pages; User-Developed CGI Scripts; Appendices: Perl; Python; PHP; Apache; Annotated Sample Configuration Files; Index.
Subtitle on cover: The nonstop Webserver.
Includes index.
Keywords: OpenVMS; Operating systems (Computers).; Web servers; Electronic books